Effect of video lag on laparoscopic surgery: correlation between performance and usability at low latencies. Issue 2 (3rd July 2016) - Kumcu, Asli; Vermeulen, Lotte; Elprama, Shirley A.; Duysburgh, Pieter; Platiša, Ljiljana; Van Nieuwenhove, Yves; Van De Winkel, Nele; Jacobs, An; Van Looy, Jan; Philips, Wilfried
Abstract: Background: Few telesurgery studies assess the impact of latency on user experience, low latencies are often not studied despite evidence of negative effects, and some studies recruit inexperienced subjects instead of surgeons without evidence that latency affects both groups similarly. Methods: Fifteen trainees and fourteen laparoscopic surgeons conducted two tasks on a laparoscopy home‐trainer at six latencies below 200 milliseconds (ms). Completion time and usability (perceived awareness of latency, inefficiency, disturbance, adaptability, and impact on patient safety) were measured. Results: Weak correlation between completion time and usability was found. There was significant deterioration in performance and user experience at 105 ms added latency. Surgeons were more negatively affected. Conclusion: Objective measures insufficiently describe the impact of latency therefore standard measures of user experience should be incorporated in studies. Even low latencies may be detrimental to laparoscopic surgery. Results from non‐experts cannot predict the impact of latency on experienced surgeons. Copyright © 2016 John Wiley & Sons, Ltd.